Brain state regulation during normal development: intrinsic activity fluctuations in simultaneous EEG-fMRI - Lüchinger, Rafael; Brandeis, Daniel (NeuroImage, 2012)
Brain maturation in adolescence is mirrored by the EEG as a pronounced decrease in low frequency activity. This EEG power attenuation parallels reductions of structural and metabolic markers of neuronal maturation (i.e., gray matter loss and decrease of absolute cerebral glucose utilization). However, it is largely unknown what causes these electrophysiological changes, and how this functional reorganization relates to other functional measures such as the fMRI BOLD signal. In this study, we used simultaneously recorded EEG and fMRI to localize hemodynamic correlates of fluctuating EEG oscillations and to study the development of this EEG-BOLD coupling. Furthermore, the maturational EEG power attenuation was directly compared to BOLD signal power maturation. Both analyses were novel in their developmental perspective and aimed at providing a functional lead to EEG maturation. Data from 19 children, 18 adolescents and 18 young adults were acquired in 10min eyes-open/eyes-closed resting states. Our results revealed that both EEG and BOLD amplitudes strongly decrease between childhood and adulthood, but their functional coupling remains largely unchanged. The global reduction of absolute amplitude of spontaneous slow BOLD signal fluctuation is a novel marker for brain maturation, and parallels the globally decreasing trajectories of EEG amplitudes, gray matter and glucose metabolism during adolescence. Further, the absence of thalamocortical EEG-BOLD coupling in children together with age-related normalized thalamic BOLD power increase indicated maturational changes in brain state regulation.